2013
DOI: 10.3109/0886022x.2013.777929
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Renal Function Using Cystatin C Level in the Patients Receiving Cisplatin-Based Chemotherapy

Abstract: Objective: There are some data regarding the role of cystatin C, a cysteine proteinase inhibitor, in determining the glomerular filtration rate (GFR) more accurately. We aimed to evaluate the correlation of serum cystatin C levels with the serum creatinine levels and GFR calculated by Cockcroft-Gault and modification of diet in renal disease (MDRD) formulations in the patients who received cisplatin-based chemotherapy. We also intended to demonstrate its potential use in the early prediction of the renal funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…Furthermore, in several malignancies, the serum cystatin C levels are elevated, probably related to its nature as a cysteine protease inhibitor [15] and this phenomenon is associated with more aggressive forms of tumors [16]. Our data are consistent with those from other studies reporting the serum cystatin C levels increase in cancer patients.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in several malignancies, the serum cystatin C levels are elevated, probably related to its nature as a cysteine protease inhibitor [15] and this phenomenon is associated with more aggressive forms of tumors [16]. Our data are consistent with those from other studies reporting the serum cystatin C levels increase in cancer patients.…”
Section: Discussionsupporting
confidence: 91%
“…Several novel biomarkers such as NGAL, cystatin‐C, and KIM‐1 have been proposed for early detection of cisplatin associated AKI. Although conflicting, it seems that urine NGAL may be the best marker among them [Gaspari et al ., ;Lin et al ., ; Nan‐Ya et al ., ; Mishra et al ., ; Kos et al ., , ]. Therefore, we assessed urine NGAL in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The CKD-EPI equation is now accepted the most accurate estimating method for GFR prediction [9,10]. Matsushita et al investigated more than 1 million adults from 25 general population cohorts and they found that CKD EPI had better outcomes than MDRD to predict mortality but these populations had especially chronic kidney disease or end stage renal disease [11]. One of the recent studies about this topic published by Janowitz et al They investigated about 2500 patients who had GFR results calculated with chromium-51 (51Cr) EDTA excretion in cancer patients.…”
Section: Discussionmentioning
confidence: 99%